CHESS enables quantitative comparison of chromatin contact data and automatic feature extraction - Galan, Silvia (Nat Genet, 2020)
Dynamic changes in the three-dimensional (3D) organization of chromatin are associated with central biological processes such as transcription, replication, and development. The comprehensive identification and quantification of these changes is therefore fundamental to our understanding of evolutionary and regulatory mechanisms. Here, we present CHESS (Comparison of Hi-C Experiments using Structural Similarity), an algorithm for the comparison of chromatin contact maps and automatic differential feature extraction. We demonstrate the robustness of CHESS to experimental variability and showcase its biological applications on: i) inter-species comparisons of syntenic regions in human and mouse; ii) intra-species identification of conformational changes in Zelda-depleted Drosophila embryos; iii) patient-specific aberrant chromatin conformation in a diffuse large B-cell lymphoma sample, and, iv) the systematic identification chromatin contact differences in high-resolution Capture-C data. In summary, CHESS is a computationally efficient method for the comparison and classification of changes in chromatin contact data.